Skill-biased labor market reforms and international competitiveness - Hans-Jörg Schmerer (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
This paper proposes a multi-industry trade model with integrated capital and goods markets. Labor market imperfections in line with Mortensen and Pissarides (Job Creation and Job Destruction in the Theory of Unemployment, 1994) give rise to unemployment and a channel for the government to influence markets through institutional changes. Labor market interventions feedback into the product market through changes in a country's competitiveness. Moreover, the distinction between high- and low-skill workers facilitates the analysis of skill-biased institutional changes that have stronger impact on certain skill groups. The comparative static exercise in this paper shows that high-skilled benefit from low-skill biased labor market reforms through higher wages. Lower labor costs reduce unemployment of the low-skilled and increases the reforming country's competitiveness. One-sided labor market interventions have feedback effects through adjustments at the extensive margin, which affect all workers at home and abroad irrespective of their level of skill. Governments in the non-reforming countries may react to this loss in competitiveness by initiating cooperative labor market reforms instead.
Keywords: E24; F16; J6; 330; FDI; globalization; search unemployment; labor market institutions; Direktinvestition; Globalisierung; Arbeitsmarktpolitik; Beschäftigungseffekt; Institutioneller Wandel; Theorie der Arbeitslosigkeit; Suchtheorie